A Scrutiny onThe Factors Affecting the Participation of Women Doing Sports and Not Doing sports in Sportive Events - Kadir Pepe; Ali Osman Kıvrak; Barbaros Serdar Erdoğan; Şirin Pepe (Selcuk University, 2019)
The study has been conducted in order to scrutinize the factors affecting the participation of women doing sports and not doing sports in sportive events. The population of the study is constituted by Selcuk University, Mehmet Akif Ersoy University, Uludağ University, and Gazi University, with the thought that we can find the individuals from all sections of the Turkish society all together and its sampling group consists of the female students studying at those universities. The data were obtained from written sources and by means of the questionnaire method. A questionnaire oriented to the objective has been developed. The understandability of the questionnaire as well as the validity and reliability of its scope were ensured. The questionnaire's CronbachAlpha reliability coefficient was found as 0,60. The coefficient is a valid coefficient according to the researchers as well. The questionnaires were filled in through one-to-one discussions in the sampling group by means of the random sampling method. Total 828 women, being 538 doing sports and 290 not doing sports, took part in the study in its state mentioned above. The data obtained were transferred to the computer environment for statistical transaction. As the statistical process, the Chi-Square test processes were conducted for identifying the frequency, %, Crosstab, and differences. In the determination of the differences, 0,05 was accepted as the level of significance. Upon the assessment of the data obtained, it was determined that the factors affecting  women's participation in sportive events are religious reasons, family pressure, government policy, the  fact the some branches of sports are not suitable for the physical properties of women, the fact that sportive events inflict damage on their beauties, presence of no suitable areas and venues to perform sports, and the inability of sports culture to take place within the society etc. and  that significant differences are present at the 0,05 statistical significance level in the views of the women doing sports and not doing sports in regards to some questions. We can conclude that there are religious, familial, political, physiological, cultural, and spatial factors affecting the participation of women in sportive events.             Keywords: Woman, Sportive event, Participation, Factor